2008
DOI: 10.3177/jnsv.54.483
|View full text |Cite
|
Sign up to set email alerts
|

Choline Deprivation Induces Hyperhomocysteinemia in Rats Fed Low Methionine Diets

Abstract: Summary To clarify the relationship between dietary choline level and plasma homocysteine concentration, the effects of choline deprivation on plasma homocysteine concentration and related variables were investigated in rats fed a standard (25%) casein (25C) diet or standard soybean protein (25S) diet. Using the 25S diet, the time-dependent effect of choline deprivation and the comparative effects of three kinds of lipotropes were also investigated. Feeding rats with the choline-deprived 25S diet for 10 d sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…It appears unlikely that the limited effect of betaine is solely due to the supplementation level of betaine. We previously demonstrated that guanidinoacetic acid-induced hyperhomocysteinemia was almost completely suppressed by betaine supplementation at a level of 0.34% (12) and that choline deprivation-induced hyperhomocysteinemia was completely suppressed by betaine supplementation at a level of 0.28% (5). Therefore, the 1% supplementation level of betaine used in the present study appears to be relatively high, although a dose-response experiment is needed to confirm the effect of betaine.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It appears unlikely that the limited effect of betaine is solely due to the supplementation level of betaine. We previously demonstrated that guanidinoacetic acid-induced hyperhomocysteinemia was almost completely suppressed by betaine supplementation at a level of 0.34% (12) and that choline deprivation-induced hyperhomocysteinemia was completely suppressed by betaine supplementation at a level of 0.28% (5). Therefore, the 1% supplementation level of betaine used in the present study appears to be relatively high, although a dose-response experiment is needed to confirm the effect of betaine.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, deficiencies of certain vitamins such as folate, vitamin B-6 and vitamin B-12 cause hyperhomocysteinemia, since these vitamins participate in the metabolism of homocysteine as enzyme cofactors (2)(3)(4). Furthermore, deprivation of choline, a vitamin-like compound, also induces hyperhomocysteinemia due to betaine deficiency ( 5 ). Hyperhomocysteinemia caused by vitamin deficiencies can be easily prevented by administration of the deficient vitamins, but other treatments are also required to suppress hyperhomocysteinemia due to genetic defects or mutations of homocysteine-metabolizing enzymes.…”
mentioning
confidence: 99%
“…Varela-Moreiras et al ( 6 ) first demonstrated that choline deprivation in the diet, which contained methionine at a level of 0.2%, increased serum homocysteine concentration. We also showed that choline deprivation gave rise to hyperhomocysteinemia in rats fed a 10% casein diet (10C) or 25% soybean protein diet, whereas it did not elevate plasma homocysteine concentration in rats fed a 25% casein diet ( 7 ). It is apparent that choline-deprivationinduced hyperhomocysteinemia is associated with cho-line deficiency within the body.…”
mentioning
confidence: 69%
“…It has been shown that deficiencies of some vitamins such as folate, vitamin B 12 , and vitamin B 6 cause hyperhomocysteinemia, since folate and vitamin B 12 are cofactors of MS and vitamin B 6 is a cofactor of CBS (1)(2)(3). We have demonstrated that choline deprivation of low-methionine diets also causes hyperhomocysteinemia mainly due to the deficiency of betaine, which is formed from the vitamin-like compound choline ( 7 ).…”
mentioning
confidence: 82%
“…Our previous study showed that choline deprivation of low-methionine diets such as 10C and 25S resulted in hyperhomocysteinemia in rats (7). In the present study, we therefore used both 10C and 25S as basal diets to induce hyperhomocysteinemia by choline deprivation, because the supplemental effect of folate alone or in combination with serine may differ depending on the type and level of dietary protein.…”
Section: Discussionmentioning
confidence: 99%